Integritas Pemoderasi Pengaruh Profesionalisme Auditor Terhadap Kualitas Audit Pada Kantor Akuntan Publik Kota Medan - Agus Tina; Eka Nurmala Sari (Universitas Islam Bandung, 2021)
This study aims to test and prove empirically about the effect of professionalism to audit quality wich is moderated by integrity. This study is quantitative study with associative approach. Survey method was used by giving questionnaires to the auditors who work in public accounting firm in Medan. Probability sampling was chosen to by 60 persons as sample. The Data was analyzed by structural equation model partial least square (SEM-PLS). The results showed that the competence has no effect on audit quality. Professionalism has no effect on audit quality. But integrity could moderated the effect of professionalism to audit quality